2003
DOI: 10.1002/anie.200351949
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature Organometallic Synthesis of Soluble and Crystalline ZnO Nanoparticles of Controlled Size and Shape

Abstract: Nanomaterials made easy! The facile oxidation of [Zn(c‐C6H11)2] at room temperature in an organic solvent containing long‐chain amine ligands leads to the formation of size‐ and shape‐controlled crystalline ZnO nanoparticles (see picture). These particles, in the form of nanodisks and nanorods of low size dispersity in the 3–10 nm size range, are fully soluble in organic solvents (e.g., THF) and photoluminescent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
1
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 220 publications
(146 citation statements)
references
References 25 publications
4
140
1
1
Order By: Relevance
“…As opposed to what was pointed out in other studies [33,41,43], the size and shape controls are not affected by the concentration of zinc precursor. Instead, the concentration of benzyl alcohol seems to play a role.…”
Section: Structural and Morphological Characterizationcontrasting
confidence: 99%
“…As opposed to what was pointed out in other studies [33,41,43], the size and shape controls are not affected by the concentration of zinc precursor. Instead, the concentration of benzyl alcohol seems to play a role.…”
Section: Structural and Morphological Characterizationcontrasting
confidence: 99%
“…We recently reported a direct organometallic route to prepare ZnO colloidal solutions containing nanoparticles of controlled size and shape. 38 We have also shown that dibenzylideneacetone derivatives of palladium and platinum can be used as precursors to yield metal nanoparticles of uniform sizes in the range 1.2-2.5 nm by submitting solutions of these compounds to CO or H 2 in the presence of a stabilizing agent as such as polymers or organic ligands. [39][40][41] We demonstrate in this paper that these Pd and Pt organometallic complexes can effectively be used as precursors to surface doping tin nanoparticles through very mild conditions and with an accurate control of morphology.…”
Section: Introductionmentioning
confidence: 95%
“…41,42 It consists in the addition of Zn(c-C 6 H 11 ) 2 solid to a THF solution containing the lithium (sodium) precursor and octylamine (OA) as stabilizer. The proportion of Li (Na) was varied from 1 to 10 mol% compared to Zn.…”
Section: Synthesismentioning
confidence: 99%
“…28,29,37 In previous works, we evidenced the interest of an organometallic synthesis based on the Zn(c-C 6 H 11 ) 2 complex for the preparation of ZnO nanoparticles of controlled size and shape. 41,42 This method takes advantage of the exothermic reaction of the organometallic precursor with water, the kinetics of which is well controlled by the ligand present in the reaction solution. Importantly, this method only leads to the formation of ZnO nanoparticles and cyclohexane.…”
Section: Introductionmentioning
confidence: 99%